Sugar-sweetened beverages in Nigeria: Affordability and expenditure and price elasticities - Darsamo, Arnalda Vanessa (School of Economics, 2022)
This research examines how consumers in Nigeria respond to income and price changes of carbonated soft drinks (CSDs). I first analysed the trend in CSD and fruit juice affordability between 2005 and 2018. I subsequently estimated the own-price, cross-price and income elasticities of sugar, CSDs, chocolate drinks, milk and sachet water for Nigeria in 2013, 2016 and a pooled sample. I used the relative income price to examine CSD and fruit juice affordability over time in Nigeria for both off-trade and on-trade consumption. For estimating the own-price, cross-price and expenditure elasticities, I used the Nigeria Household Survey, Panel (2013 and 2016) data, using the Almost Ideal Demand System. I applied Deaton's unit value model and used unit values as prices and used the Heckman procedure to correct for selection bias. For CSDs, the own-price elasticities ranged from - 0.8 to -1.8. All income (approximated by household expenditure) elasticities were positive implying all the commodities are normal goods. The income elasticity of demand lies at approximately 0.4 for CSDs. The results suggest that Nigeria can curb the consumption of excess sugar, in particular excess sugar in CSDs, by raising the price by implementing an excise tax on the sugar content in CSDs. Future research should estimate the health gains and government revenue that can be generated from such a tax. Such estimates are crucial to motivate for a sugar tax.